Development Initiatives and Challenges for Sustainable Resource Management and Livelihood in the Lake Tana Region of Northern Ethiopia. (1st July 2002) - Teshale, Berhanu; Lee, Ralph; Zawdie, Girma
Poverty reduction programmes often falter when development initiatives are not conceived and implemented in the framework of sustainability. Using the case of the Lake Tana region in north-western Ethiopia, this paper discusses the environmental, social and economic consequences of urbanisation and development activities in the region. The paper notes the threat to sustainable development posed by the growth of social and economic activities in the region. At issue is the current practice of discharging untreated industrial, municipal and domestic waste into the Lake and the adverse effects of this on the sustainability of the use value of the Lake; on prospects for urban development in the region; and on the livelihood of traditional communities around the Lake. The paper sets in context the issue of environmental management and development in the region, and points out the need for more research to inform policy, so that interventions in the form of development initiatives can be directed in ways that enhance sustainability of the aquatic and agro-ecosystems of the region.